Public budgetary roles in Iran: perceptions and consequences. Issue 1 (9th December 2020) - Jalali Aliabadi, Farzaneh; Gal, Graham; Mashyekhi, Bita
Abstract : Purpose: This study aims to examine the public budgeting process in the higher education and research sectors of Iran. It focuses on the actors' budgetary roles and uses their perspectives to identify deficiencies in the budgeting process that cause delays in the transition to a performance-based system. Design/methodology/approach: This study uses an interpretive research paradigm. It applies the grounded theory methodology to analyze the interviews conducted with those responsible for budgeting at Iranian public universities and research institutes (PURI). The results are interpreted using Wildavsky's (1964) budgetary roles paradigm. Findings: Using Wildavsky's (1964) paradigm, "spenders" and "guardians" are identified and their perceptions about the public budgeting process are described. The results suggest a decoupling between the actors' perceptions based on their budgetary roles. Spenders consider budgeting as a negotiation-based process, while guardians' decisions are largely based on "outputs" and "information." This study demonstrates that the disagreement over the perceived budget process was due to different budgetary roles. This disagreement leads to delays in the transformation of the budget process in Iranian PURI. Research limitations/implications: While efforts are made to obtain a sample of individuals with different roles and responsibilities, the selection is limited by subjects' willingness and availability. Therefore, sample size and diversity are potential limitations of this study. Practical implications: When organizations attempt to transition to performance-based budgeting (PBB), it is critical to understand the current budgeting process to identify potential impediments. Understanding these impediments allows for alternate approaches to be considered. This is particularly important for universities that are mostly funded by the government (such as those in Iran). The results of this study show that the contradictory perceptions among budget actors have a significant impact on budgeting transition and require attention to understand budgeting decisions. Originality/value: This study contributes to the budgeting literature in three ways. First, it examines the impact of endogenized shared values among budget participants on the budgeting transition process. Second, by focusing on budgetary roles, it contributes to the literature by examining disagreement on the perceived budgeting process and its implications for transforming the process into PBB. Finally, to the authors' knowledge, this is the first study to examine the public budgeting process in a developing country – Iran.